2017
DOI: 10.14260/jemds/2017/113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Etomidate and Thiopentone Sodium as Anaesthetic Agents for Modified Electroconvulsive Therapy

Abstract: BACKGROUNDElectroconvulsive Therapy (ECT) is considered to be one of the most commonly used procedure in psychiatry practice.This prospective study was designed to compare the effects of etomidate and sodium thiopentone used in ECT on seizure threshold and duration, haemodynamics, recovery from ECT and immediate side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Propofol had pain on injection as the main side effect, Etomidate had myoclonus and Thiopentone had cough as side effects. Studies conducted by Patil AP et al [19] , Donthu B et al [20] , Mir AH et al [13] showed similar results. These studies are in concurrence with our study.…”
Section: Resultsmentioning
confidence: 55%
“…Propofol had pain on injection as the main side effect, Etomidate had myoclonus and Thiopentone had cough as side effects. Studies conducted by Patil AP et al [19] , Donthu B et al [20] , Mir AH et al [13] showed similar results. These studies are in concurrence with our study.…”
Section: Resultsmentioning
confidence: 55%